Elder abuse from the perspectives of elderly people: - Heravi-Karimooi, M; Anoosheh, M; Foroughan, M; Sheykhi, M; Hajizadeh, E; Seyed-Bagher-Maddah, M; Mohammadi, E; Ahmadi, F (Advances in Nursing & Midwifery, 2008)
Background Domestic elderly abuse is a type of family violence and is now well recognized as a public health and a societal problem worldwide. Purpose This phenomenological study was conducted to understand the basic concept of abuse in the elderly. Methods Benner’s interpretive phenomenology was chosen to describe elderly women’s understanding of the concept of abuse in the elderly in Tehran. Ten elders between 68 and 87 were interviewed 2-5 times in an unstructured format. They explained their experiences regarding this phenomenon. The interviews were tape-recorded and gathered data were transcribed and thematically analyzed. Results 3 themes were derived including the nature of abuse toward the elderly, living with abuse outcomes and facing with abuse toward the elderly. Conclusion The findings can show a clear picture of abuse experiences in the study group. Keywords: Elder abuse, Battered women, Qualitative research.